METHOD FOR OBTAINING A THREE-DIMENSIONAL IMAGE IN PATIENTS WITH CONGENITAL UNILATERAL CLEFT LIP AND PALATE - Murtazaev Sayidalo Murtazaevich; Rustam Azimzhanovich Amanullayev; Mirkhayidov Miraziz Mirkholik; Boltakhodjaeva Lola Muradovna (Scholar Express Journals, 2022)
A unilateral cleft nose can be "caused" by displacement of the anterior nasal spine and caudal septum. The cleft alar base is in the normal position but retracted, while the unadjusted alarum is laterally displaced. Changes with surgery include anterior movement of the alar base cleft, but also include medial movement of the week base of the alarum and columella. The symmetry of the correction, including retrusion of the alar base, was stable over time and independent of alveolar bone grafting
Keywords: cleft lip; cleft palate; congenital anomaly; classification